A FRAMEWORK FOR ASSESSING THE LOW-FARE MODEL IN THE AIRLINE INDUSTRY - Huettinger, Maik; Adomavičius, Benas (Ekonomika, 2011)
Despite the popularity of the “low-fare” (or sometimes called “no-frills”) airline business model, no comprehensive framework has ever been developed to evaluate the level of implementation of this business model. In the paper, we propose a framework for evaluating the extent to which an airline has implemented a “low-fare” business model. The framework (SFC) consists of three dimensions: (a) strategic direction factors; (b) pricing factors; (c) cost structure factors (COFA). Strategic direction factors primarily focus on the top-level strategic decisions of an airline: growth concepts, the range of flights, spatial strategy and target group selection. These factors serve to differentiate the “lowfare” airlines from more traditional rivals on a strategic level. Pricing factors evaluate differentiators at the level of market offer: relative ticket prices, the number of booking classes, ticket restrictions, interlining, penalties, non-ticket income and target load levels. These factors differentiate the “low-fare” business model on the value proposition level. Cost structure factors focus on internal cost-saving measures designed to significantly reduce the average costs per passenger: outsourcing, aircraft type homogeneity, levels of aircraft utilization, labour factors, airport costs, distribution and in-flight arrangements. The SFC framework allows academics and practitioners to coherently analyze and identify gaps between current and desired levels of the “low-fare” business model implementation.